Two types of muscarinic acetylcholine receptors in Drosophila and other arthropods. - Collin, C.; Hauser, F.; Gonzalez de Valdivia, E.; Li, S.; Reisenberger, J.; Carlsen, E.M.; Khan, Z.; Hansen, N.O.; Puhm, F.; Søndergaard, L.; Niemiec, J.; Heninger, M.; et al. (Cellular and molecular life sciences. CMLS, 2013)
Muscarinic acetylcholine receptors (mAChRs) play a central role in the mammalian nervous system. These receptors are G protein-coupled receptors (GPCRs), which are activated by the agonists acetylcholine and muscarine, and blocked by a variety of antagonists. Mammals have five mAChRs (m1-m5). In this study, we cloned two structurally related GPCRs from the fruit fly Drosophila melanogaster, which, after expression in Chinese hamster ovary cells, proved to be muscarinic acetylcholine receptors. One mAChR (the A-type; encoded by gene CG4356) is activated by acetylcholine (EC50, 5 × 10(-8) M) and muscarine (EC50, 6 × 10(-8) M) and blocked by the classical mAChR antagonists atropine, scopolamine, and 3-quinuclidinyl-benzilate (QNB), while the other (the B-type; encoded by gene CG7918) is also activated by acetylcholine, but has a 1,000-fold lower sensitivity to muscarine, and is not blocked by the antagonists. A- and B-type mAChRs were also cloned and functionally characterized from the red flour beetle Tribolium castaneum. Recently, Haga et al. (Nature 2012, 482: 547-551) published the crystal structure of the human m2 mAChR, revealing 14 amino acid residues forming the binding pocket for QNB. These residues are identical between the human m2 and the D. melanogaster and T. castaneum A-type mAChRs, while many of them are different between the human m2 and the B-type receptors. Using bioinformatics, one orthologue of the A-type and one of the B-type mAChRs could also be found in all other arthropods with a sequenced genome. Protostomes, such as arthropods, and deuterostomes, such as mammals and other vertebrates, belong to two evolutionarily distinct lineages of animal evolution that split about 700 million years ago. We found that animals that originated before this split, such as cnidarians (Hydra), had two A-type mAChRs. From these data we propose a model for the evolution of mAChRs.